Osteoarthritic process modifies expression response to NiTi alloy presence - Válková, Lucie; Ševčíková, Jana; Pávková Goldbergová, Monika; Weiser, Adam; Dlouhý, Antonín (Journal of materials science. Materials in medicine, 2018)
Nickel-titanium alloy (nitinol, NiTi) is a biomaterial with unique thermal shape memory, superelasticity and high damping properties. Therefore NiTi has been used in medical applications. In this in vitro study, the effect of NiTi alloy (with two surface modifications - helium and hydrogen) on gene expression profile of selected interleukins (IL-1β, IL-6 and IL-8) and matrix metalloproteinases (MMP-1 and MMP-2) in human physiological osteoblasts and human osteoarthritic osteoblasts was examined to respond to a question of the different behavior of bone tissue in the implantation of metallic materials in the presence of cells affected by the osteoarthritic process. The cells were cultivated in contact with NiTi and with or without LPS (bacterial lipolysaccharide). Changes in expression of target genes were calculated by 2-ΔΔCt method. An increased gene expression of IL-1β in osteoarthritic osteoblasts, with even higher expression in cells collected directly from the metal surface was observed. In case of physiological osteoblasts, the change in expression was detected after LPS treatment in cells surrounding the disc. Higher expression levels of IL-8 were observed in osteoarthritic osteoblasts after NiTi treatment in contact with alloy, and in physiological osteoblasts without relation to location in combination of NiTi and LPS. IL-6 was slightly increased in physiological osteoblastes after application of LPS. MMP-1 expression level was obviously significantly higher in osteoarthritic osteoblasts with differences regarding the metal surface and location. MMP-2 expression was decreased in both cell lines after LPS treatment. In conclusion, results of present study show that the NiTi alloy and the treatment by LPS, especially repeated doses of LPS, change the gene expression of selected ILs and MMPs in human osteoblast cell cultures. Some of the changes were depicted solely to osteoarthritic osteoblasts.
Keywords: Gene Expression Regulation; nikl; Nickel; Lipopolysaccharides; osteoartróza; testování materiálů; osteoblasty; Materials Testing; lipopolysacharidy; titan; cytokiny; Titanium; Osteoblasts; Osteoarthritis; kultivované buňky; lidé; biokompatibilní materiály; Humans; regulace genové exprese; Cells, Cultured; Cytokines; Biocompatible Materials